Novel two-stage fluidized bed-plasma gasification integrated with SOFC and chemical looping combustion for the high efficiency power generation from MSW: a thermodynamic investigation - Jiang, Peng; Mahmud Parvez, Ashak; Meng, Yang; Dong, Xinyue; Xu, Mengxia; Luo, Xiang; Shi, Kaiqi; Wu, Tao (2021)
A novel municipal solid waste (MSW)-based power generation system was proposed in this study, which consists of a bubbling fluidized-bed (BFB)-plasma gasification unit, a high-temperature solid oxide fuel cell (SOFC), a chemical looping combustion (CLC) unit and a heat recovery unit. Process simulation was conducted using Aspen PlusTM and validated by literature data. The energetic and exergetic assessment of the proposed system showed that the net electrical efficiency and exergy efficiency reached 40.9 % and 36.1 %, respectively with 99.3 % of carbon dioxide being captured. It was found that the largest exergy destruction took place in the BFB-Plasma gasification unit (476.5 kW) and accounted for 33.6 % of the total exergy destruction, which is followed by the SOFC (219.1 kW) and then CLC (208.6 kW). Moreover, the effects of key variables, such as steam to fuel ratio (STFR), fuel utilization factor (Uf), current density and air reactor operating temperature, etc., on system performance were carried out and revealed that the system efficiency could be optimized under STFR = 0.5, Uf = 0.8 and air reactor operating temperature of 1000 ºC. Furthermore, the proposed process demonstrated more than 14% improvement in net electrical efficiency in comparison with other MSW incineration and/or gasification to power processes.